PENGARUH PENGGUNAAN MEDIA AUDIO VISUAL BERBASIS LAGU DAN MODEL MAKE A MATCH TERHADAP HASIL BELAJAR SISWA KELAS IV SDN BERAN 4 NGAWI PADA MATERI KERAGAMAN BUDAYA - Hani'atul Muawanah; Hela Putri Izzatin Nisa; Hamidah, Nabila Hafsah; Roni Adi Saputra; Shinta Dwi Nur Fatimah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of using song-based audiovisual media combined with the Make a Match learning model on the learning outcomes of fourth-grade students at SDN Beran 4 Ngawi on the topic of Cultural Diversity. This study employed a quantitative approach using a quasi-experimental method with a Nonequivalent Control Group Design. The sample consisted of Class IV A as the experimental class and Class IV B as the control class, selected using a saturated sampling technique. Data were collected through pretests and posttests and analyzed using normality tests, homogeneity tests, an Independent Samples t-test, and N-Gain analysis. The results showed a significant effect of using song-based audiovisual media and the Make a Match learning model on students' learning outcomes, as indicated by a significance value (Sig. 2-tailed) of 0.000 < 0.05. The N-Gain test results showed that the experimental class obtained an N-Gain score of 0.774 (77.4%), categorized as high, while the control class obtained a score of 0.605 (60.5%), categorized as moderate. Therefore, the use of song-based audiovisual media combined with the Make a Match learning model is effective in improving students' learning outcomes on the topic of Cultural Diversity.